Análise de blogs de pessoas com deficiência: acessibilidade e barreiras no processo de inclusão - Silva, Amanda Caroliny Costa da [UNESP] (2014)
The efforts for inclusion involve the search for a democratic society, which allows the full exercise of the citinzenship by all people. Regardless the achievements, prejudices continue to permeate the human reality. By considering the overlap between social inclusion and digital inclusion, arising from the character that the information and communication technologies assumenowadays, and being this a research field still underesplored, it was recognized the need to look into such relationship through the perspective of person with disabilities. Through a descriptive-exploratory qualitative documental essay, the objective was to describe and analyze the form whereby persons with disabilities report on their blogs the acessibility and barriers to the social inclusion in their routines. There were select in picked up three Blogs in a search site, whose authors were people with physical disabilities, visual impairment and hearing impairment. When the reports were submitted to content analyzing, two different categories were defined: (1) acessibility in everyday life of persons with disabilities (2) barriers in the routine of the person with disabilities, both subdivided in physical, attitudinal and sensorial conditions. When reporting common situations such as working, hanging out, watching TV, sports practicing, among others, the bloggers have contributed with evidences of challenges and achievements in ths process of inclusion that were noticed in their everyday life. Highlights to hints and personal strategies related to their major functionality, assistive technologies and problems in acessing these means, environments and adpatations conceived or not under the perspective of the universal design and, lastly, beliefs and atitudes regarding the person with disabilities that empower or hamper the independence and potentiality of any individual, especially in the conditions of a person with disability. The blogges denoted being aware about...